EVIDENCE FOR 182HF IN THE EARLY SOLAR SYSTEM AND CONSTRAINTS ON THE TIMESCALE OF TERRESTRIAL ACCRETION AND CORE FORMATION - Harper C.L.; Jacobsen S.B. (My University, 1996)
We present evidence from tungsten (W) isotopic measurements consistent with the presence of live 182Hf (T1 = 9 Ma) in the early solar system. This is based on the observation of a well-resolved deficit of about four parts in ten thousand in the ratio 182W183W in W separated from the Toluca iron meteorite. This deficit is interpreted as an excess in the terrestrial standard composition due to radiogenic growth of 182W. If the initial 182Hf180Hf ratio in the solar system is <2 x 10-4, then some of this growth must have taken place in the silicate portion of the Earth which has Hf # 10-20x the chondritic ratio. This fractionation is a consequence of siderophile element segregation to form the Earth's core, which most likely occurred contemporaneously with accretion. Thus W isotopes may provide useful constraints on the chronology of terrestrial core formation and accretion. The magnitude of the observed effect is broadly consistent with (1) the predicted initial abundance of 182Hf in the solar system based on a Type II supernova source model for most of the radionuclides with half-lives less than 17 Ma 129I (Harper, 1995, 1996b) and (2) the Wetherill (1986) accretion calculations (which predict an #10 Ma mean age of accretion). Alternate explanations involving isotopic heterogeneity and α-decay of 186Os cannot explain the magnitude of the observed effect. Neutron transport code calculations by Masarik and Reedy (1994) indicate the observed anomaly is too large by more than a factor of six to be due to neutron capture on W during space exposure. However, due to unknown uncertainties in the W nuclear input data, this possibility is not definitively excluded and must be checked by direct experimental calibration.In principle, the 182Hf-182W system offers the most geochemically direct way to determine the timescale for the Earth's accretion and core formation with excellent time resolution, but requires precise calibration based on internal 182Hf-182W isochron studies of meteorites of independently known age. We explore aspects of isotopic evolution in continuous fractionation models under boundary assumptions describing the degree of equilibration between mantle W and accreted W during siderophile partitioning, and find these to be highly significant for interpretation of measured effects. Our initial results hint towards the possibility of a more rapid timescale than obtained in Safronov-Wetherill-type models. A fast accretion timescale would be in agreement with gas drag and density-wave-accelerated accretion models (e.g., Ward, 1986, 1989, 1993). However, other interpretations are possible.